Exploring the Nexus between Refugee Integration and National Security: A Case Study of Eastleigh, Kamukunji Constituency in Nairobi County, Kenya - Erick, Ochieng Otieno; Felistus, Mwikali; Norvy, Paul (Top Journal of Public Policy and Administration (TJPPA), 2023)
This study examines the relationship between refugees and national security in Kenya, with a specific focus on Eastleigh, Kamukunji Constituency, Nairobi County. The study explores whether refugees pose a threat to national security, the connection between refugees and terrorism, and whether Kenya's open-door policy on refugees undermines national security. The research used a mixed-methods approach, including questionnaires and one-on-one interviews with refugees and key stakeholders such as UNHCR, Danish Refugee Council, and the Ministry of Interior and Coordination of National Government. The findings indicate that refugees are linked to terrorism in Kenya and effective policies, laws, and approaches are required to address insecurity. The study recommends non-refoulement refugee policies and laws, refugee settlements, local integration, voluntary repatriation, and measures against errant refugees to be implemented to ensure national security. This research also suggests that the United Nations, World Bank, and IMF should support peacekeeping missions and strengthen government institutions to counter displacement, resettlement and integration of refugees who cannot return to their country of nationality. This research contributes to theoretical, practical and policy-based knowledge on refugees and national security in Kenya.